Alkali-silica reactivity of alkali-activated concrete subjected to ASTM C 1293 and 1567 alkali-silica reactivity tests. (September 2019) - Li, Zihui; Thomas, Robert J.; Peethamparan, Sulapha
Abstract: This paper presents an experimental investigation of the alkali-silica reactivity of alkali-activated concrete (AAC). Some researchers suggest that the high alkalinity of the pore solution could make AAC more susceptible to alkali-silica reaction (ASR) than comparable ordinary Portland cement (OPC) concrete, perhaps even with aggregates that are normally considered non-reactive. Many have further questioned the suitability of standardized ASR test methods for use with AAC. In an attempt to resolve this controversy, the authors subjected OPC, alkali-activated fly ash (AAF), and alkali-activated slag (AAS) concrete made with both reactive and non-reactive aggregates to accelerated and long-term ASR test protocols (ASTM C1567 and C1293). Paradoxically, some AAS mixtures with non-reactive aggregates showed significant expansion while AAF mixtures with reactive aggregates expanded minimally. AAS mixtures with reactive aggregates underwent extremely high expansions. Microstructural evaluation using scanning electron microscopy revealed significant cracking but did not identify ASR gel in the majority of specimens.